2023
DOI: 10.3389/fpls.2023.1280771
|View full text |Cite
|
Sign up to set email alerts
|

Legume-grass mixtures increase forage yield by improving soil quality in different ecological regions of the Qinghai-Tibet Plateau

Feng Luo,
Wenhui Liu,
Wenbo Mi
et al.

Abstract: IntroductionInformation on the relationship between soil quality and forage yield of legume-grass mixtures in different ecological regions can guide decision-making to achieve eco-friendly and sustainable pasture production. This study’s objective was to assess the effects of different cropping systems on soil physical properties, nitrogen fractions, enzyme activities, and forage yield and determine suitable legume-grass mixtures for different ecoregions.MethodsOats (Avena sativa L.), forage peas (Pisum sativu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…This was contrary to the findings of Zhu et al (2020) who concluded that soil bacterial diversity was higher at lower elevations and suggested that this pattern was related to higher vegetation diversity at lower elevations. This result may have been due to differences in climatic conditions within specific altitudinal zones (Press, 2009), differences in sensitivity of soil bacteria and fungi to the environment, or differences in the initial microbial communities in different ecological zones (Luo et al, 2023). In addition, soil fungal and bacterial α-diversity in the same cropping pattern differed significantly across ecological zones.…”
Section: Influence Of the Ecoregions On The Soil Microbial Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was contrary to the findings of Zhu et al (2020) who concluded that soil bacterial diversity was higher at lower elevations and suggested that this pattern was related to higher vegetation diversity at lower elevations. This result may have been due to differences in climatic conditions within specific altitudinal zones (Press, 2009), differences in sensitivity of soil bacteria and fungi to the environment, or differences in the initial microbial communities in different ecological zones (Luo et al, 2023). In addition, soil fungal and bacterial α-diversity in the same cropping pattern differed significantly across ecological zones.…”
Section: Influence Of the Ecoregions On The Soil Microbial Communitiesmentioning
confidence: 99%
“…( 4) Soil bacteria and fungi differ in their sensitivity to the environment. Due to the different adaptability of crops to the environment, differences in the biological nitrogen fixation capacity of leguminous crops in different ecological regions leads to differences in soil nitrogen cycling and utilization, indirectly affecting the diversity of soil microorganisms (Luo et al, 2023).…”
Section: Key Factors Affecting the Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological nitrogen fixation (BNF) by legumes is an important way to replenish soil nitrogen ( Yao et al., 2019 ). Mixed grass and legume forage cropping systems, which significantly optimize the cropping system by increasing plant diversity and improving soil health ( Crème et al., 2015 ; Zhao et al., 2015 ), are a way to develop sustainable ecological agriculture ( Luo et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%